Pengembangan Lembar Kerja Peserta Didik Berbasis Problem Based Learning pada Muatan Pelajaran Bahasa Indonesia Sekolah Dasar - Isnawati Isnawati; Muhammad Nurwahidin; Siti Samhati; Riswandi Riswandi (Universitas Pendidikan Mandalika, 2023)
This study aims to develop and analyze the feasibility and effectiveness of student worksheets based on problem-based learning in the Indonesian language lesson content, theme 1, class V of elementary school. This study used the Research and Development (R&D) method with the Brog & Gall model. The subjects in this study were determined using a purposive sampling technique and obtained as many as 25 students in class V SDN 01 Setia Negara and Negara Batin. The instrument used in this study was a multiple-choice test instrument that had been tested for validity, reliability, discriminatory power, and difficulty level of the questions. The results of this study indicated that student worksheets based on problem-based learning were very feasible and effective to use. Test the effectiveness of using N-Gain with a calculation result 0.60 with independent test results t test sig. 0.01<0.05. Based on this research, problem-based learning student worksheets on developed Indonesian language lesson content were feasible and effective for improving student learning outcomes on theme 1 class V of elementary school.